Identification of IbeR as a Stationary-Phase Regulator in Meningitic Escherichia coli K1 that Carries a Loss-of-Function Mutation in rpoS. (20th January 2009) - Chi, Feng; Wang, Ying; Gallaher, Timothy K.; Wu, Chun-Hua; Jong, Ambrose; Huang, Sheng-He
Abstract : IbeR is a regulator present in meningitic Escherichia coli strain E44 that carries a loss-of-function mutation in the stationary-phase (SP) regulatory gene rpoS . In order to determine whether IbeR is an SP regulator in E44, two-dimensional gel electrophoresis and LC-MS were used to compare the proteomes of a noninvasive ibeR deletion mutant BR2 and its parent strain E44 in the SP. Four up-regulated (TufB, GapA, OmpA, AhpC) and three down-regulated (LpdA, TnaA, OpmC) proteins in BR2 were identified when compared to E44. All these proteins contribute to energy metabolism or stress resistance, which is related to SP regulation. One of the down-regulated proteins, tryptophanase (TnaA), which is regulated by RpoS in other E. coli strains, is associated with SP regulation via production of a signal molecule indole. Our studies demonstrated that TnaA was required for E44 invasion, and that indole was able to restore the noninvasive phenotype of the tnaA mutant. The production of indole was significantly reduced in BR2, indicating that ibeR is required for the indole production via tnaA . Survival studies under different stress conditions indicated that IbeR contributed to bacteria stress resistance in the SP. Taken together, IbeR is a novel regulator contributing to the SP regulation.